2019
DOI: 10.1111/ahg.12347
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean fever (MEFV) gene profile and a novel missense mutation (P313H) in Iranian Azari‐Turkish patients

Abstract: Background: Familial Mediterranean fever (FMF) is common in Azari-Turkish people, one of the biggest ethnic groups in Iran. In this study, we sought to investigate the mutation spectrum of the MEFV gene and any genotype-phenotype correlations. Methods and materials: 400 unrelated Azari-Turkish FMF patients were analyzed in this study. Mutations in exons 2, 3, 5, and 10 of the MEFV gene were investigated using direct Sanger sequencing, and their correlations with the clinical features of the patients were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our study indicated that 19.4% of parents were consanguineous, which was similar to Rostamizadeh et al (21). However, Bidari et al (22) and Celikel et al ( 13) reported a higher rate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study indicated that 19.4% of parents were consanguineous, which was similar to Rostamizadeh et al (21). However, Bidari et al (22) and Celikel et al ( 13) reported a higher rate.…”
Section: Discussionsupporting
confidence: 88%
“…In the genetic results, 12.50% of patients were homozygous, 47.50% were compound heterozygous, 20% were heterozygous, 2.50% had complex genotypes, and 17.50% had no mutation. Regarding the type of genes, although there are Turkish, Iranian, Egyptian, and Lebanese studies that mentioned a higher frequency of no mutation (12,16,17,(19)(20)(21) In the present study, there was no significant relationship between fever and abdominal pain with any of the mutations. Although there are Iranian and Turkish investigations (15)(16)(17)21) that noticed M694V mutations in patients with fever and abdominal pain, Mansour et al (19) found the E148Q mutation in these patients.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Following the exclusion of 428 articles due to duplication and irrelevant to our subject, 16 articles published between 2004 and 2020, involving 4,256 Iranian FMF patients, were included in this systematic review. Nine studies were performed on patients from different regions [8][9][10][11][12][13][14][15][16], six studies were performed on Azeri Turkish patients living in the northwest [17][18][19][20][21][22], and one study was performed in the southwest of Iran [23] (Table 1). The ratio of male to female varied from 0.57 to 1.68.…”
Section: Resultsmentioning
confidence: 99%
“…1 Distribution of common MEFV gene mutations in different regions of Iran. It should be noted that only in nine articles it was possible to extract mutations based on the geographical location of patients (Mohammadnejad and Farajnia [20] & Sabokbar et al [14] & Hosseini et al [10] & Gharesouran et al [19] & Bonyadi et al [18] & Salehzadeh [22] & Ebadi et al [15] & Bagheri and AbdiRad [17] & Rostamizadeh et al[21]). Therefore, data presented here is taken from those nine articles…”
mentioning
confidence: 99%